Food and Cash Crop Productivities and Poverty Reduction in Ghana (Global Journal of Human-Social Science, 2022)
Food and cash crop productivities growth provide food and improve smallholder farmers' income to reduce poverty. Crop farmers poverty rate is disaggregated into food and cash crop type but beyond 2006 the poverty rate is not disaggregated which is addressed by this study. Food and cash crops have different growth paths and unequal pathways towards poverty. The paper estimates the poverty rates among food and cash crop farmers and examines their productivities effect on poverty. The estimated poverty measures are explained by crop output value per hectare of land using Panel logistic two stage instrumental variable fixed and random effects models with data from the fifth and sixth rounds of the Ghana Living Standards Survey (GLSS). The study finds cash crop output value increased by 330% more than food crop output value which increased by 190% to provide food and income towards poverty reduction between 2005 and 2013. The findings reveals using a poverty line of ₡1314 ($219) poverty among food crop farmers declined from 59% in 2005 to 39% by 33.9% in 2013. Poverty among cash crop farmers fell from 35% in 2005 to 24% by 31.4% in 2013 to reveal food crop farmers have higher poverty rates than cash crop farmers and both food and cash crops have considerable importance towards poverty reduction. Furthermore, an increase of food crops productivity by 1% reduces poverty headcount ratio, poverty gap, and poverty severity by -0.19%, -0.41% and -0.81% respectively. A 1% increase in cash crop productivity reduces probability of poverty headcount ratio, poverty gap, and poverty severity by -0.28%, -0.44% and -0.88% respectively. Food and cash crops poverty rates have declined significantly through provision of food and income and both production systems reduce poverty with inelastic estimates which should be supported with resources and skills such as improved crop varieties, production methods due to low use of recommended practices, capacity building, and market access to increase productivity to provide food and income towards poverty reduction.
Keywords: crop productivity; poverty; wellbeing